Eco-friendly sucrose and polyvinyl acetate – based polymeric systems - Puková, Kateřina; Machotová, Jana; Mikulášek, Petr; Rückerová, Adéla (My University, 2017)
The work is focused on the synthesis of aqueous polymeric dispersions based on polyvinyl acetate and sucrose by emulsion polymerization technique. These polymeric latexes can be used in the field of sustained release fertilizer encapsulation or as an ecological paper glue with subsequent low biological disposal. The main objective of this work was to bond covalently sucrose into polyvinyl acetate ensure intended feature of these materials is their expected biodegradation of the polymer mainly in the soil environment. Was searched for optimal ratio between the polymer and the simple sugar in the alkaline medium has been investigated so that the resulting latex exhibits good water solubility, sufficient bond strength, and atmospheric humidity stability. Using infrared spectroscopy, binding of sucrose to the polymer chain of vinyl acetate has been demonstrated.
Ekologicky šetrné polymerní systémy na bázi sacharózy a polyvinylacetátu
Keywords: polyvinyl acetate; sucrose; eco-friendly polymer; polyvinylacetát; sacharóza; ekologický polymer